2009
DOI: 10.1007/s10571-009-9420-4
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Mitochondrial Functions in Organophosphate Induced Delayed Neuropathy in Rats

Abstract: Acute exposure to organophosphates induces a delayed neurodegenerative condition known as organophosphate-induced delayed neuropathy (OPIDN). The mechanism of OPIDN has not been fully understood as it does not involve cholinergic crisis. The present study has been designed to evaluate the role of mitochondrial dysfunctions in the development of OPIDN. OPIDN was induced in rats by administering acute dose of monocrotophos (MCP, 20 mg/kg body weight, orally) or dichlorvos (DDVP, 200 mg/kg body weight, subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 66 publications
7
30
0
Order By: Relevance
“…Typical signs and symptoms of OPIDN include tingling of the hands and feet, followed by sensory loss, progressive muscle weakness and flaccidity of the distal skeletal muscles of the lower and upper extremities and ataxia [3][4][5]. In pathology, OPIDN is classified as a centralperipheral sensorimotor axonopathy, which is characterized by distal axonal degeneration in spinal cord and peripheral nerves and swollen axons containing aggregations of microtubules, neurofilaments, smooth endoplasmic reticulum and multivesicular vesicles [6,7]. At present, there is a lack of effective means to treat OPIDN, so it is very important to find new effective therapy means to treat OPIDN.…”
Section: Introductionmentioning
confidence: 99%
“…Typical signs and symptoms of OPIDN include tingling of the hands and feet, followed by sensory loss, progressive muscle weakness and flaccidity of the distal skeletal muscles of the lower and upper extremities and ataxia [3][4][5]. In pathology, OPIDN is classified as a centralperipheral sensorimotor axonopathy, which is characterized by distal axonal degeneration in spinal cord and peripheral nerves and swollen axons containing aggregations of microtubules, neurofilaments, smooth endoplasmic reticulum and multivesicular vesicles [6,7]. At present, there is a lack of effective means to treat OPIDN, so it is very important to find new effective therapy means to treat OPIDN.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which dichlorvos provokes myopathic and neurodegenerative effects has not been defined, but some work suggests that it is related to mitochondrial dysfunction [54]. The changes in metabolic processes and potential mitochondrial dysfunction (see below) observed in response to dichlorvos exposure make this a plausible mechanism for the damage induced in the worms.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of AChE is likely a key player as many of the perturbed processes involve neuronal signaling, and the observed behavior changes are consistent with increased accumulation of acetylcholine. The observed changes in the expression of genes involved in energy metabolism suggest that dichlorvos is disrupting mitochondrial function, which has been shown to be a mechanism for neuronal degeneration [54]. Calcium homeostasis is potentially another process perturbed by dichlorvos exposure, but it is unclear whether dichlorvos directly or indirectly perturbs calcium homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…Study by Masoud et al also suggested that the activity of mitochondrial succinate dehydrogenase was obviously decreased in the brain of monocrotophos (MCP)-or dichlorvos (DDVP)-exposed rats and the activities of mitochondrial complex I (NADH dehydrogenase), II (succinate dehydrogenase), and IV (cytochrome oxidase) in isolated mitochondria from different brain regions were all significantly decreased. 21 As mentioned above, the oxidative stress of nervous system induced by TOCP might damage the mitochondrial Figure 6. The activity of mitochondrial succinate dehydrogenase by mitochondria from hens' nerve tissues following administration of tri-ortho-cresyl phosphate (TOCP).…”
Section: Atp Has Beenmentioning
confidence: 93%